PENGARUH LITERASI KEUANGAN, PEMBELAJARAN MANAJEMEN KEUANGAN, DAN OVERCONFIDENCE TERHADAP PERILAKU BERINVESTASI MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - Nur Afni Kristianingsih; Agung Listiadi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The objective of this study was to examine and analyze the effect of financial literacy, financial management learning, and overconfidence on the investment behaviour of students of the Faculty of Economics, State University of Surabaya. The sample consisted of 73 respondents taken by using the purposive sampling technique. Data were analyzed using multiple linear regression. The results showed that, simultaneously, financial literacy, financial management learning, and overconfidence had a significant effect on the investment behaviour of students of the Faculty of Economics, State University of Surabaya. Keywords: financial literacy, financial management learning, investment behaviour, overconfidence